Cross-script orthographic and phonological preview benefits. Issue 1 (January 2018) - Jouravlev, Olessia; Jared, Debra
The present experiment examined the use of parafoveally presented first-language (LI) orthographic and phonological codes during reading of second-language (L2) sentences in proficient Russian-English bilinguals. Participants read English sentences containing a Russian preview word that was replaced by the English target word when the participant's eyes crossed an invisible boundary located before the preview word. The use of English and Russian allowed us to manipulate orthographic and phonological preview effects independently of one another. The Russian preview words overlapped with English target words in (a) orthography ( ВЕЛЮР [vʲɪˈlʲʉr]– BERRY ), (b) phonology ( БЛАНК [blank]– BLOOD ), or (c) had no orthographic or phonological overlap ( КАЛАЧ [kɐˈlat͡ɕ]– BERRY ; ГЖЕЛЬ [ɡʐɛlʲ]– BLOOD ). The results of this study showed a clear and strong benefit of the parafoveal preview of Russian words that shared either orthography or phonology with English target words. This study is the first demonstration of cross-script orthographic and phonological parafoveal preview benefit effects. Bilinguals integrate orthographic and phonological information across eye fixations in reading, even when this information comes from different languages.